2019
DOI: 10.1051/bioconf/20191501012
|View full text |Cite
|
Sign up to set email alerts
|

The effect of foliar fertilizing on ecological optimization of the application of fungicides on the productivity and phenolic complex composition of grapes

Abstract: One of the ways to reduce the pesticidal burden in mature ampelocenoses is the use of foliar bio-preparations of multifunctional action. We studied the influence of growth bioregulators “Albit” and “Mival-Agro” at reduced by 25–50% fungicidal load on productivity and phenolic complex composition (using the HPLC method) of Vitis vinifera “Asma” (Crimean autochthonous table cultivar), “Cabernet Sauvignon” and table grapes of complex genetic structure “Moldova”, grown in the mountain-valley seaside region of Crim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…It has been shown that bacterial endophytes induce systemic plant resistance due to the accumulation of phenolic compounds [16]. We observed an increase in the content of phenolic components in grapes when biological preparations were used in agrotechnological schemes [12,17].…”
Section: Introductionmentioning
confidence: 61%
“…It has been shown that bacterial endophytes induce systemic plant resistance due to the accumulation of phenolic compounds [16]. We observed an increase in the content of phenolic components in grapes when biological preparations were used in agrotechnological schemes [12,17].…”
Section: Introductionmentioning
confidence: 61%
“…To develop effective protection of plants from diseases (including Apple trees from scab), it is necessary to evaluate the effect of protection agents in a specific zone [6]. Thus, immunity inducers proved to be an effective tool in apple tree protection systems against scab in Abkhazia, significantly reducing the degree of scab development [7].…”
Section: _________________________________mentioning
confidence: 99%
“…The important role of calcium is also determined in the grape storage. It is known that the more calcium is contained in a berry, the greater and longer its preservation period, due to the increased resistance of products to pathogens and the content of secondary metabolitesphenolic substances, stilbenes in particular [13].…”
Section: Introductionmentioning
confidence: 99%